Perinatal Outcomes of Hypertensive Pregnancy: A Case Control Study - Acharya, Niraj; Dhungana, Diwas; Gupta, Veena (Journal of Nepalgunj Medical College, 2019)
Background: Hypertensive disorders of pregnancy (HDP) are one of the maternal diseases that cause the most detrimental effects to the mother and the fetus. Objective: This study was conducted to compare the perinatal outcomes of neonates delivered by hypertensive mothers and normal mothers. Methods: This comparative hospital based study was conducted in Nepalgunj Medical College Teaching Hospital, Kohalpur from December 2014 to December 2015. Fifty mothers fulfilling the inclusion criteria and their fetal outcome in form of still birth and newborn babies were taken for the study and 50 healthy mothers with normotensive pregnancies and their newborn babies or fetal outcome were taken as control. They were followed up till their hospital stay in NICU or postnatal ward and final outcomes were noted. Results: The prevalence of HDP in our hospital was 2.16%. Among neonates, 27(54%) in case group and 9(18%) in control group were low birth weight which is statistically significant. It was found that 18(36%) neonates in case group and 7(14%) neonates in control group were IUGR(Intrauterine growth retardation). Seventeen (34%) neonates in case group were preterm as compared to 2(4%) neonates in control group (p value < 0.001). Conclusion: Pregnancies complicated by hypertension were characterized by an increase in the rate of preterm delivery and low birth weight infants compared with normal pregnancies.